Tourism as a Tool of Recovery of Ukrainian Communities: Economic and Mental Healing - Anna Romanova; Sean McGinley (Socio-Cultural Management Journal)
Introduction. The full-scale Russian invasion of Ukraine in 2022 has resulted in devastating damage to infrastructure, the economy, and human capital. Alongside these visible effects, the war has inflicted profound psychological trauma, including heightened anxiety, chronic stress, and post- traumatic stress disorder (PTSD), which are expected to have long-term consequences for Ukraine’s recovery. In this context, tourism is examined as a tool for dual recovery – economic revitalisation and mental health restoration. Objective and Methods. The purpose of the paper is to investigate how the tourism sector can contribute to the recovery of Ukrainian communities during and after the war. The methodological foundation is based on Growth Pole Theory and the Tourism-Led Growth Hypothesis (TLGH). The study employs a mixed-methods approach, including analysis of global post-conflict tourism case studies, comparative tourism investment assessments, and content analysis of Ukrainian policies on community recovery. Results. The findings demonstrate that tourism development contributes to economic regeneration through infrastructure enhancement, job creation, and support for local entrepreneurship. Simultaneously, tourism plays a vital role in supporting the psychological well- being of war-affected populations by enhancing resilience and reducing PTSD symptoms, anxiety, depression, sleep disorders, and aggressive behaviour. Developed Complex Model of the Impact of Tourism on Community Recovery after Traumatic Events illustrates the integration of economic and mental health benefits leveraged by tourism and impacting human capital development. The paper presents a comprehensive conceptual model of tourism’s impact on community recovery. Conclusions. Tourism can serve as a strategic instrument for Ukraine’s integrated recovery. Tourism simultaneously fosters economic development and mental resilience and offers immediate and long-term benefits. The paper recommends targeted initiatives to develop therapeutic, nature-based, and memorial tourism programs as part of Ukraine’s reconstruction strategy.